Anti-β2GPI domain 1 antibodies stratify high risk of thrombosis and late pregnancy morbidity in a large cohort of Chinese patients with antiphospholipid syndrome. Issue 185 (January 2020) - Liu, Tingting; Gu, Jieyu; Wan, Liyan; Hu, Qiongyi; Teng, Jialin; Liu, Honglei; Cheng, Xiaobing; Ye, Junna; Su, Yutong; Sun, Yue; Chi, Huihui; Zhou, Zhuochao; et al.
Abstract: Introduction: Anti-β2GPI-Domain 1 (β2GPI-D1) antibodies are considered to be a pathogenic subset of anti-β2GPI antibodies and have been strongly associated with thrombosis and pregnancy morbidity in patients with antiphospholipid syndrome (APS). We evaluated the clinical utility of anti-β2GPI-D1 IgG antibodies for stratifying the risk of thrombosis and/or pregnancy morbidity (PM) in a cohort of Chinese patients with APS and also assessed its correlation with the Global Anti-Phospholipid Syndrome Score (GAPSS). Materials and methods: Sera and plasma from 192 consecutive APS patients, 17 aPL carriers, 193 patients with other systemic autoimmune diseases, and 120 healthy controls were collected and the presence of aCL IgG/IgM, anti-β2GPI IgG/IgM and anti-β2GPI-D1 IgG antibodies were assessed by chemiluminescence assays (CIA). Detection of LAC was performed according to international guidelines with the use of screening, mixing and confirmation tests. Anti-phosphatidylserine-prothrombin (aPS/PT) IgG and IgM antibodies were detected by commercial ELISA kits. Results: Anti-β2GPI-D1 IgG antibodies showed high specificity (97.12%) and moderate sensitivity (64.32%) for the diagnosis of APS. Anti-β2GPI-D1 antibodies levels were significantly higher in patients with triple aPL positivity than in those with double (P < 0.001) and single positive aPL (P < 0.001) and correlated well with the GAPSS (rho = 0.60, P < 0.001). Anti-β2GPI-D1 antibodies presented with a higher prevalence and higher titers in patients with late pregnancy morbidity (≥10 weeks) and thrombotic APS compared to those with early pregnancy (<10 weeks) morbidity. Higher anti-β2GP1-D1 antibodies titers effectively distinguished APS from other autoimmune diseases. Conclusion: This study suggests a predictive role of anti-β2GPI-D1 IgG antibodies as a strong risk factor for both thrombotic and obstetric APS (OAPS), especially for stratification comparing early PM with late PM and thrombosis. Highlights: Anti-β2GPI-D1 IgG antibodies showed high specificity and moderate sensitivity for the diagnosis of APS. Anti-β2GPI-D1 antibody levels were highest in patients with triple aPL positivity and correlated well with the GAPSS. Anti-β2GPI-D1 IgG antibodies as an important factor for stratification comparing early PM with late PM and thrombosis. Higher anti-β2GP1-D1 antibody titers effectively distinguished APS from other autoimmune diseases.